2009
DOI: 10.1016/j.febslet.2009.07.054
|View full text |Cite
|
Sign up to set email alerts
|

N9L and L9N mutations toggle Hha binding and hemolysin regulation by Escherichia coli and Vibrio cholerae H‐NS

Abstract: a b s t r a c tProteins of the Hha/YmoA family co-regulate with H-NS the expression of virulence factors in Enterobacteriaceae. Vibrio cholerae lacks Hha-like proteins and its H-NS (vcH-NS) is unable to bind Hha, in spite of the conservation of a key residue for Hha binding by Escherichia coli H-NS (ecH-NS). Exchange of the residues in position 9 between vcH-NS and ecH-NS strongly reduces Hha binding by ecH-NS and introduces it in vcH-NS. These mutations strongly affect the repression of the hemolysin operon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This finding has led to speculation that Hha-like proteins indirectly exert regulatory control by altering the oligomerization properties of H-NS. The notion that Hha and YdgT act through H-NS to modulate gene expression is supported by experimental evidence that Hha/H-NS complex formation is required for silencing of the hlyCABD operon in E. coli, which encodes the ␣-hemolysin toxin (28,31). Complicating this model are reports that Hha can independently bind to specific regulatory sequences within the hilA promoter from S. Typhimurium and the esp operon of enterohemorrhagic E. coli (22,23,32,33).…”
Section: The Bacterial Nucleoid-associated Proteins Hha and H-ns Joinmentioning
confidence: 52%
See 1 more Smart Citation
“…This finding has led to speculation that Hha-like proteins indirectly exert regulatory control by altering the oligomerization properties of H-NS. The notion that Hha and YdgT act through H-NS to modulate gene expression is supported by experimental evidence that Hha/H-NS complex formation is required for silencing of the hlyCABD operon in E. coli, which encodes the ␣-hemolysin toxin (28,31). Complicating this model are reports that Hha can independently bind to specific regulatory sequences within the hilA promoter from S. Typhimurium and the esp operon of enterohemorrhagic E. coli (22,23,32,33).…”
Section: The Bacterial Nucleoid-associated Proteins Hha and H-ns Joinmentioning
confidence: 52%
“…In one model, Hha exerts regulatory control solely through its interaction with H-NS (28,31). In the second model, Hha can bind DNA and influence transcription independently of H-NS (22,23,32,33).…”
Section: Mutations Of H-ns At Residues Ile-11 and Arg-12 Abolish The mentioning
confidence: 99%
“…Thus, a modest change in the relative orientation of the long H3 helices at the N-terminal dimerization site may result in the recognition of significantly different DNA structural features. We have previously shown that the complementary mutations Asn9?Leu and Leu9?Asn in full-length E. coli H-NS and V. cholerae H-NS substantially change the electrophoretic mobility of the nucleoprotein complexes, confirming that even small changes in the N-terminal dimerization domain have a large effect on DNA binding [33]. Furthermore, Asn9 and Arg12 are involved in binding of Hha, a protein that modifies the capacity of H-NS to recognize horizontally acquired DNA [2].…”
Section: Discussionmentioning
confidence: 92%
“…Sample preparation and characterization (U-13 C, 15 N)-labeled full-length H-NS and H-NS 1-47 from E. coli were obtained and purified as described elsewhere [7,33,34]. Saturated ammonium sulfate was slowly added to 70% saturation to 70-80 lM H-NS samples with gentle stirring at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Hha interacts exclusively with the N-terminal dimerization domain (NTD) of H-NS. The NTD is completely included in a construct formed by residues 2-47 (H-NS 46 ) (19,45). The solution structure of the complex formed between Hha and H-NS 46 could not be determined by classical NOE-based methods because of extensive broadening of key NMR signals upon complex formation.…”
Section: Resultsmentioning
confidence: 99%